2015
DOI: 10.1016/j.scitotenv.2014.12.070
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of volcanic rock powder for application in agriculture as soil a remineralizer

Abstract: Mineralogical and geochemical characteristics of volcanic rock residue, from a crushing plant in the Nova Prata Mining District, State of Rio Grande do Sul (RS), Brazil, in this work named rock powder, were investigated in view of its potential application as soil ammendment in agriculture. Abaut 52,400 m(3) of mining waste is generated annually in the city of Nova Prata without a proper disposal. The nutrients potentially available to plants were evaluated through leaching laboratory tests. Nutrient leaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 13 publications
2
28
0
7
Order By: Relevance
“…The ADI and HI of As were calculated to evaluate the potential human health risk associated with vegetable consumption. Similar ananlyses were previously reported in other studies (Arenas-Lago et al, 2013; Cerqueira et al, 2011, 2012; Hower et al, 2013; Ramirez-Andreotta et al, 2013b; Ramos et al, 2015; Ribeiro et al, 2013b; Rodriguez-Iruretagiiena et al, 2015; Silva et al, 2011; Martinello et al, 2014). …”
Section: Resultssupporting
confidence: 91%
“…The ADI and HI of As were calculated to evaluate the potential human health risk associated with vegetable consumption. Similar ananlyses were previously reported in other studies (Arenas-Lago et al, 2013; Cerqueira et al, 2011, 2012; Hower et al, 2013; Ramirez-Andreotta et al, 2013b; Ramos et al, 2015; Ribeiro et al, 2013b; Rodriguez-Iruretagiiena et al, 2015; Silva et al, 2011; Martinello et al, 2014). …”
Section: Resultssupporting
confidence: 91%
“…As expected from the literature (GILL, 2015), plagioclase was the most abundant (greatest peak in Figure 1) and among the most soluble minerals in the RM (RAMOS et al, 2015). The study by FARIA (2008) demonstrated that the crystal grains are richer in Na at their periphery …”
Section: Resultssupporting
confidence: 78%
“…In addition, basalts are on average rich in nutrients such as phosphorus, magnesium, and calcium, whose application on cropland could lead to considerable additional benefits [3,[39][40][41]. These are particularly interesting in the case of tropical regions where cation and geo-nutrient depleted soils feature deficits considering optimal plant growth rates leading to recent efforts to assess rock product fertilizer alternatives [42], which could also improve soil hydrology. Furthermore, projected shortages in K supply (as potash) could shift the focus to alternative rock products [43].…”
Section: Discussionmentioning
confidence: 99%